Nilotinib-Associated Destructive Thyroiditis - Suhalia Bakerywala; Monica D. Schwarcz; Michael D. Goldberg; Guy Valiquette; Irene A. Weiss (Case Reports in Endocrinology)
Protein tyrosine kinase inhibitors are currently an important drug class in the treatment of leukemia. They represent targeted cancer therapy and have become the treatment of choice in chronic myeloid leukemia. Tyrosine kinases are enzymes expressed in multiple tissues and are involved in several signaling pathways influencing cellular growth. Below we describe a patient who developed an unusual complication of tyrosine kinase inhibitor therapy: thyrotoxicosis due to destructive thyroiditis. We review the pathophysiology of tyrosine kinase inhibitor-induced thyroid dysfunction particularly with regard to new second-generation tyrosine kinase inhibitors.